2021
DOI: 10.1002/ange.202014337
|View full text |Cite
|
Sign up to set email alerts
|

S‐Adenosyl‐l‐ethionine is a Catalytically Competent Analog of S‐Adenosyl‐l‐methionine (SAM) in the Radical SAM Enzyme HydG

Abstract: Radical S‐adenosyl‐l‐methionine (SAM) enzymes initiate biological radical reactions with the 5′‐deoxyadenosyl radical (5′‐dAdo.). A [4Fe‐4S]+ cluster reductively cleaves SAM to form the Ω organometallic intermediate in which the 5′‐deoxyadenosyl moiety is directly bound to the unique iron of the [4Fe‐4S] cluster, with subsequent liberation of 5′‐dAdo.. We present synthesis of the SAM analog S‐adenosyl‐l‐ethionine (SAE) and show SAE is a mechanistically equivalent SAM‐alternative for HydG, both supporting enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The importance of active site forces in controlling radical intermediates is further demonstrated by a study involving the SAM analog S-adenosylethionine (SAE) in which the methyl group of SAM is replaced by an ethyl group (43). This change does not alter the observed regioselectivity of photocleavage: Photolysis of PFL-AE-SAE, like PFL-AE-SAM, gives rise to a 5 ′ -dAdo r trapped in the active site, while photolysis of HydG-SAE results in homolysis of the Sethyl bond to produce an ethyl radical ( r CH 2 CH 3 ) trapped in the active site (43,44). Compared to the methyl radical produced from HydG-SAM photolysis, the ethyl radical is more constrained in the active site, and like the larger 5 ′ -dAdo r in PFL-AE, the ethyl radical is indefinitely stable at 77 K (44).…”
Section: Photoinduced Generation Of a Methyl Radicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of active site forces in controlling radical intermediates is further demonstrated by a study involving the SAM analog S-adenosylethionine (SAE) in which the methyl group of SAM is replaced by an ethyl group (43). This change does not alter the observed regioselectivity of photocleavage: Photolysis of PFL-AE-SAE, like PFL-AE-SAM, gives rise to a 5 ′ -dAdo r trapped in the active site, while photolysis of HydG-SAE results in homolysis of the Sethyl bond to produce an ethyl radical ( r CH 2 CH 3 ) trapped in the active site (43,44). Compared to the methyl radical produced from HydG-SAM photolysis, the ethyl radical is more constrained in the active site, and like the larger 5 ′ -dAdo r in PFL-AE, the ethyl radical is indefinitely stable at 77 K (44).…”
Section: Photoinduced Generation Of a Methyl Radicalmentioning
confidence: 99%
“…Compared to the methyl radical produced from HydG-SAM photolysis, the ethyl radical is more constrained in the active site, and like the larger 5 ′ -dAdo r in PFL-AE, the ethyl radical is indefinitely stable at 77 K (44). The ethyl radical trapped in the HydG active site anneals to an organometallic species denoted E in which the ethyl group is covalently bound to the unique iron of the [4Fe-4S] cluster (Figure 10) (43).…”
Section: Photoinduced Generation Of a Methyl Radicalmentioning
confidence: 99%
“…In addition, the alkylcobalamin must be able to react with the substrate radical. The ability to generate the DOA⋅ radical from SAM analogues has been previously demonstrated for Se ‐adenosylselenomethionine ( Se SAM), SAE, allyl‐SAM, nucleobase analogues, and the sulfoxide derivative of SAH [36–38,84,85] . Alkylcobalamins have been described in some studies, including enzyme‐catalysed C−C bond formation [86,87] …”
Section: Resultsmentioning
confidence: 99%
“…Particularly in drug synthesis the ever‐expanding chemical space of radical SAM enzymes is of interest for challenging reactions, e. g. stereo‐ and regioselective methylation of sp 3 ‐carbons. In addition to the possibility of broadening the diversity of radical SAM MT products by transferring alternative alkyl chains, this might be interesting in terms of using SAM analogues for mechanistic studies as has been shown before [36,37,84,85] . Together with the increasing number of available enzyme structures, it might be possible to design enzyme variants with a broader or altered substrate range, as has been shown for MATs and conventional MTs [88–91] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation